Using post-mortem computed tomography to identify traumatic cranial lesions in small stranded odontocetes euthanised via ballistics - Boys RM; Stewart RO; Kot BCW; Lye G; Beausoleil NJ; Stockin KA (Taylor and Francis Group on behalf of the New Zealand Veterinary Association, 2025)
Aims: To describe the pathophysiology caused by ballistics applied to the head of stranded cetaceans that required euthanasia and use this information to infer the likely welfare implications of these real-life euthanasia events. Methods: Post-mortem computed tomography (PMCT) imaging was conducted on six cetacean carcasses of five different species that were submitted for dissection following ballistics euthanasia. No animals were euthanised for the purpose of this study. All data were collected opportunistically at stranding events where euthanasia was a priori deemed necessary by the Department of Conservation (DOC) in partnership with indigenous Māori (iwi). The cranial damage assessed included osseous lesions at entry and exit wounds, intracranial bone fractures and intracranial projectile fragments. Potential welfare implications were inferred based on the likelihood of instantaneous insensibility occurring due to direct physical disruption to the brainstem. Additionally, basic stranding data were collected from DOC incident reports including whether animals were refloated prior to the decision for euthanasia. We also gathered information from the marksperson involved on how the ballistics method was employed, equipment used, and animal insensibility assessed at each stranding event. Results: PMCT results suggest that two animals were likely instantaneously insensible, three had a moderate chance of being instantly insensible and one had a low chance of instantaneous insensibility. In one case, the marksperson reported a faster time to insensibility/death than was judged likely to have occurred from PMCT. In only two cases were the criteria for verifying insensibility reported as being checked. The likelihood of instantaneous insensibility occurring was affected by shot placement/aim and characteristics of the projectile used. Conclusions: Euthanasia is a critical option for severely compromised cetaceans. While most animals examined were probably rapidly insensible following shooting, cranial trauma and thus confidence in the efficacy of ballistics seemed to vary with shot placement, aim, equipment and cranial anatomy. Clinical relevance: Verification of insensibility immediately following shooting, by assessing reflex responses as recommended, is crucial to ensure humane emergency management. PMCT provides an effective non-destructive tool to validate field methods for assessing the efficacy of euthanasia.
Keywords: Animal welfare; euthanasia; cetacean; computed tomography; insensibility